Living in a digital culture: The need for theological reflection - Cloete, Anita Louisa (HTS teologiese studies, 2015)
Today our lives are filled with technology through which we communicate, work, play and even engage with for making meaning. This implies the pervasive presence of digital media as an integral part of our everyday life. Although studies on media are mostly done by sociology and communication students, living in a digital age has significant implications for theological reflections. Despite this being the case there is gap in terms of a religious response to technology. In response to this, the aim of this article is to stimulate theological reflections with regard to living in a digital culture. This is achieved by raising theological questions in the hope that theology could take a proactive role in these discussions. The implications of living in a digital culture are quite vast; therefore, the focus will be limited to how a community is formed and sustained, and the possible implications for the church as community.